Strengthening Moral Values Through Religious Knowledge Integration: Insights from Madrasah Ibtidaiyah - Nurhidayati, Siti; Sentosa, Sedya (Bidayatuna, 2024)
This study explores the significance of integrating Islamic religious knowledge into moral value education for students aged 7–8 years in Madrasah Ibtidaiyah. At this critical stage of character development, understanding moral values is essential. An integrative approach ensures that religious knowledge is not only taught as theoretical content but also serves as a practical guide for daily behavior. The teaching methods employed include thematic learning, case studies, and creative projects designed to engage students and deepen their comprehension. The findings reveal that effective integration of religious knowledge and moral education helps students internalize virtuous character traits and equips them to interact positively within society. This research contributes to the development of a more holistic and relevant curriculum in the context of Islamic education.